How Corruption Puts Higher Education at Risk - Heyneman, Stephen P. (International Higher Education, 2014)
Global attention begin in the 1990s with definitions and questions as to how common education corruption was; it then expanded to include the differences from one to another region, ranging from financial corruption and student plagiarism to sexual intimidation. Once these had been mapped, the next issues concerned the degree to which education corruption might affect an economy, and the degree to which it might be addressed through changes in policy.